Change and transition on Crete : interpreting the evidence from the Hellenistic through to the Early Byzantine Period : papers presented in honour of G.W.M. Harrison - Harrison, George W. M., 1951-; Francis, Jane E., 1962-; Curtis, M. (Archaeopress Archaeology, 2023)
The theme of this volume, presented in honour of G.W.M. Harrison, whose academic contributions have enriched our perspective of Roman Crete, is change and transition, a topic that challenges some of the earlier approaches to Hellenistic and Roman Crete, and which presents a different perspective on historical events and archaeological evidence.